Essays on corporate governance and firm performance in Ghana - Antwi, Isaac Francis (2023)
This research aims to assess corporate governance compliance practices by listed firms on the Ghana Stock Exchange (GSE). A sample of 33 firms listed on the Ghana Stock exchanges was selected. The study period covers from 2009 to 2020, thus, analysing 372 firm-year observations. A corporate governance compliance index was developed based on the Ghana Security and Exchange Commission (SEC 2010), consisting of six recommended principles and 108 items to measure the corporate governance practice in the sample firms. In addition, firm performance was measured by accounting-based performance indicators (ROA) and market-based performance indicators (Tobin’s Q). The first essay analysed the corporate governance compliance levels based on the guideline principles recommended by SEC 2010 for listed firms on GSE. The results showed that compliance levels with the SEC guidelines increased over the period under analysis. The second essay examined the relationship between the level of compliance with the recommendations included in the Ghana SEC 2010 Corporate Governance Compliance guidelines and firm performance. The results indicated a negative relationship between the total corporate governance compliance and the firm performance of the listed companies measured by both ROA and Tobin’s Q. The third essay aimed to determine whether the quality of corporate governance influences firm performance. The evidence showed some mixed effects. The relationship between CG quality and firm performance depends on the mechanisms analysed and the performance measure. The study contributes to a better understanding of the corporate governance compliance level of Ghanian listed companies and the effects of individual mechanisms of corporate governance on firm performance.